Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors

Calculator Output

Simplifying
y = 5(x + -2)(x + 3)(x + -1 + -2)

Reorder the terms:
y = 5(-2 + x)(x + 3)(x + -1 + -2)

Reorder the terms:
y = 5(-2 + x)(3 + x)(x + -1 + -2)

Reorder the terms:
y = 5(-2 + x)(3 + x)(-1 + -2 + x)

Combine like terms: -1 + -2 = -3
y = 5(-2 + x)(3 + x)(-3 + x)

Multiply (-2 + x) * (3 + x)
y = 5(-2(3 + x) + x(3 + x))(-3 + x)
y = 5((3 * -2 + x * -2) + x(3 + x))(-3 + x)
y = 5((-6 + -2x) + x(3 + x))(-3 + x)
y = 5(-6 + -2x + (3 * x + x * x))(-3 + x)
y = 5(-6 + -2x + (3x + x2))(-3 + x)

Combine like terms: -2x + 3x = 1x
y = 5(-6 + 1x + x2)(-3 + x)

Multiply (-6 + 1x + x2) * (-3 + x)
y = 5(-6(-3 + x) + 1x * (-3 + x) + x2(-3 + x))
y = 5((-3 * -6 + x * -6) + 1x * (-3 + x) + x2(-3 + x))
y = 5((18 + -6x) + 1x * (-3 + x) + x2(-3 + x))
y = 5(18 + -6x + (-3 * 1x + x * 1x) + x2(-3 + x))
y = 5(18 + -6x + (-3x + 1x2) + x2(-3 + x))
y = 5(18 + -6x + -3x + 1x2 + (-3 * x2 + x * x2))
y = 5(18 + -6x + -3x + 1x2 + (-3x2 + x3))

Combine like terms: -6x + -3x = -9x
y = 5(18 + -9x + 1x2 + -3x2 + x3)

Combine like terms: 1x2 + -3x2 = -2x2
y = 5(18 + -9x + -2x2 + x3)
y = (18 * 5 + -9x * 5 + -2x2 * 5 + x3 * 5)
y = (90 + -45x + -10x2 + 5x3)

Solving
y = 90 + -45x + -10x2 + 5x3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 90 + -45x + -10x2 + 5x3
Processing time: 1 ms. 51464585 equations since February 08, 2004.   Disclaimer

Equation Calculator & Solver

Equation: Variable:
       
Hint: Selecting "AUTO" in the variable box will make the calculator automatically solve for the first variable it sees.

Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors